THE EFFECT OF LOCAL TAXES ON CAPITAL EXPENDITURE ALLOCATION WITH POPULATION SIZE AS A MODERATING VARIABLE IN SAMARINDA CITY - Sitti Rahma Sudirman; Ardhiatul Halima Tuasalamony; Wahyuni Saleh; Rahadian Cahyadi (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
This study aims to determine the effect of local tax revenue on capital expenditure allocation with population size as a moderating variable in Samarinda City. This research is a descriptive quantitative study using secondary data in the form of time series data from 2011 to 2024. The data used includes local tax revenue, capital expenditure realization, and population data of Samarinda City. The analytical methods employed are descriptive statistical analysis, simple linear regression analysis, and moderated regression analysis (MRA). The results show that local taxes have a positive and significant effect on capital expenditure. Furthermore, population size is able to moderate the relationship between local taxes and capital expenditure. These findings indicate that increased local tax revenue increases the regional government's fiscal capacity to allocate capital expenditure, while population growth strengthens the need for infrastructure and public service financing.